Serum immune profiling of patients with polycystic ovary syndrome - Mobeen, Hifsa; Kashif, Muhammad; Nadeem, Ahmed; Shahzad, Faheem; Tahir, Romeeza; Abbas, Afia; Afzal, Nadeem (Makara Journal of Health Research, 2020)
Background: Polycystic ovary syndrome (PCOS), the most prevalent hormonal disorder in females, is characterized by low levels of progesterone, which causes increased estrogen levels leading to production of various anti and auto-antibodies. This study aimed to estimate and compare levels of anti-nuclear antibodies (ANA), anti-thyroid peroxidase (anti-TPO), anti-thyroglobulin (anti-TG), and anti-islet cell antibodies (anti-ICAb) in patients with PCOS and healthy controls. Methods: The present comparative study included 82 subjects divided into two groups with 41 individuals in each group. Group I included healthy subjects, while Group II included patients diagnosed with PCOS. Blood samples were collected to determine serum levels of ANA, anti-TPO, anti-TG, and anti-ICAb using commercially available ELISA kits. Data were analyzed by using SPSS 20.0. Results: Two (4.8%) subjects in Group II had ANA, but none of the other healthy individuals had these auto-antibodies. Levels of anti-TPO were higher in Group II (6.01 IU/ml) than in Group I (5.98 IU/ml). Levels of anti-TG and anti-ICAb were higher in Group I (19.86 and 32.49 IU/ml, respectively) than in Group II (19.78 and 26.07 IU/ml, respectively). Conclusion: Levels of ANA and anti-TPO were higher in patients with PCOS than in controls. By contrast, levels of anti-TG and anti-ICAb were higher in controls than in patients with PCOS.